The Warwick Hip Trauma Evaluation –an abridged protocol for the WHiTE Study: A multiple embedded randomised controlled trial cohort study. Issue 11 (November 2012) - Griffin, X. L.; Achten, J.; Parsons, N.; Boardman, F.; Griffiths, F.; Costa, M. L.
Abstract : Fractures of the proximal femur are one of the greatest challenges facing the medical community, constituting a heavy socioeconomic burden worldwide. The National Hip Fracture Audit currently provides a framework for service evaluation. This evaluation is based upon the assessment of process rather than assessment of patient-centred outcome and therefore it fails to provide meaningful data regarding the clinical effectiveness of treatments. This study aims to capture data from the cohort of patients who present with a fracture of the proximal femur at a single United Kingdom Major Trauma Centre. Patient-centred outcomes will be recorded and provide a baseline cohort within which to test the clinical effectiveness of experimental interventions.